Evaluasi Faktor Penerimaan Pengguna Sistem Informasi E-Learning Universitas Negeri Surabaya dengan Menggunakan Metode Technology Acceptance Model (TAM) - Chafidz Rizal Ilmi; Aditya Rachmadi; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
State University of Surabaya has already implemented e-learning system with moodle base which used centrally by all of faculty to help and solving a problem during lecturer. After the system on-line, there are factors has to be improved to make e-learning system is accepted by the user. Purpose of this study is to describe the level of acceptance from information system of UNESA e-learning system and also giving improvement recommendation according to Technology Acceptance Model (TAM) Method.. Data collection in this study was used by filling out the online questionnaire. This study uses a sample of 156 respondents and uses a stratified purposive sampling technique. The results of the evaluation of this study indicated that the perceived usefulness, perceived ease of use, educational quality, service quality, information quality, satisfaction, and intention to use variable are in the high category, while the actual use variable is in the fairly high category. With the total average value of all variables of 70.85%, educational quality, service quality, intention to use, and actual use variable must get top priority to be improved because the average value of the variable percentage is still below the average value.